Vitrification of human blastocysts for couples undergoing assisted reproduction: an updated review - Sciorio, Romualdo; Tramontano, Luca; Campos, Gerard; Greco, Pier Francesco; Mondrone, Giuseppe; Surbone, Anna; Greco, Ermanno; Talevi, Riccardo; Pluchino, Nicola; Fleming, Steven (Frontiers in Cell and Developmental Biology, 2024)
Over the past 40 years there has been a worldwide critical change in the field of assisted reproduction technology (ART), leading to the increased application of single blastocyst transfer, which is extremely important to avoid the risks of multiple pregnancy and associated complications for both mother and babies. Indeed, advancements in ART over the last few decades have been obtained thanks to several improvements, including ovarian stimulation, embryo culture conditions and, of course, progress in cryopreservation methods, especially with the application of vitrification. The ability to cryopreserve human embryos has improved significantly with vitrification compared to the initially adopted slow-freezing procedures. Since the introduction of vitrification, it has become the gold standard method to effectively cryopreserve human blastocysts. However, some new protocols are now being explored, such as the short warming procedure and even shorter exposure to the equilibration solution before vitrification, which seem to provide optimal results. Therefore, the main aim of the current narrative review, will be to illustrate the benefit of vitrification as an effective method to cryopreserve the human blastocyst and to illustrate new protocols and variations which in future may increase the performance of vitrification protocols.